Effect of omega-3 fatty acids enriched diet on semen characteristics in Marwari horses - RAVI, S K; KUMAR, H; VYAS, S; NARAYANAN, K; KUMARI, S; SINGH, J; JAN, M H (The Indian Journal of Animal Sciences, 2016)
The effect of w-3 fatty acid supplementation in the diet on various characteristics of fresh and frozen semen was investigated in Marwari horses. Stallions (6) were fed a standard diet daily from week –13 to week 0 (pre- supplementation phase) followed by supplementation of fish oil, a rich source of n-3 PUFA @64 mg/kg BW from week 1 to 14 (fish oil treatment phase) in diets. Ejaculates were collected from all the stallions on weekly basis from week –5 to 0 and week 9 to 14 during pre-supplementation and fish oil treatment phase, respectively. Effect of n-3 PUFA on ejaculate volume, color and consistency; total and progressive sperm motility, seminal pH, sperm concentration, live sperm and abnormal sperm in fresh semen was non-significant. Similarly, there was no change in the percentage of sperm PTM, HOS reacted sperm, live and abnormal sperm in frozen semen. It was concluded that dietary n-3 PUFA supplementation @64mg/ kg BW to horses for 14 weeks did not affect the semen quality. However, the beneficial effects of n-3 PUFA on semen quality may require longer period of supplementation.